OmpK36-mediated Carbapenem resistance attenuates ST258 Klebsiella pneumoniae in vivo - Joshua L. C. Wong (Nature Portfolio, 2019)
Carbapenem-resistance in Klebsiella pneumoniae sequence type ST258 can be enhanced by modification of the porins OmpK35 and OmpK36. Here, Wong et al. solve the crystal structure of a clinical ST258 OmpK36 variant, elucidating the mechanism of resistance and consequences on pathogenicity in vivo.